Intermittent low platelet counts hampering diagnosis of X-linked thrombocytopenia in children: report of two unrelated cases and a novel mutation in the gene coding for the Wiskott-Aldrich syndrome protein - Samuel Souza Medina; Lúcia Helena Siqueira; Marina Pereira Colella; Gabriela Goes Yamaguti-Hayakawa; Bruno Kosa Lino Duarte; Maria Marluce Dos Santos Vilela; Margareth Castro Ozelo (BMC, 2017)
Abstract Background Thrombocytopenia can occur in different circumstances during childhood and although immune thrombocytopenia is its most frequent cause, it is important to consider other conditions, especially when there is a persistent or recurrent low platelet count. We report two cases of intermittent thrombocytopenia, previously misdiagnosed as immune thrombocytopenia. Cases presentation Both cases described were boys who presented with an intermittent pattern of thrombocytopenia, with a persistently low mean platelet volume. In both patients, peripheral blood smear revealed small platelets and flow cytometry showed low expression of Wiskott-Aldrich syndrome protein (WASP) in leucocytes. Molecular analysis of the first case identified a mutation in exon 2 of the gene coding for WASP, leading to a p.Thr45Met amino acid change and confirming the diagnosis of X-linked thrombocytopenia. In the second case, a novel missense mutation in exon 2 of the gene coding for WASP was detected, which resulted in a p.Pro58Leu amino acid change. Conclusion These two rare presentations of thrombocytopenia highlight the importance of evaluating the peripheral blood smear in the presence of recurrent or persistent thrombocytopenia and show that failing to do so can lead to misdiagnoses. Since thrombocytopenia may be found in pediatric outpatient clinic, increased awareness among general pediatricians will help to improve the differential diagnosis of this condition.